Clinical Results of Microvascular Decompression in the Treatment of Trigeminal Neuralgia - Durmuş Oğuz Karakoyun; Ümit Kocaman (Middle Black Sea Journal of Health Science, 2026)
Objective: This study aimed to evaluate the clinical outcomes of microvascular decompression (MVD) in patients with trigeminal neuralgia (TN) and to emphasize the importance of meticulous intraoperative identification of the responsible neurovascular compression.Methods: This retrospective single-center case series included 12 patients who underwent trigeminal nerve MVD between 2024 and 2025. Preoperative magnetic resonance imaging findings, intraoperative compression characteristics, pain distribution, petrosal vein management, postoperative Barrow Neurological Institute (BNI) pain intensity scores, follow-up duration, and complications were reviewed.Results: The mean age of the patients was 56 years, and nine patients were female. The mean symptom duration was 3.9 years. All patients had a preoperative BNI pain score of V. Pain was left-sided in nine patients and right-sided in three patients. The V3 division alone was involved in seven patients, and combined V2-V3 involvement was observed in five patients. The superior cerebellar artery was the most frequent compressive structure. Eleven patients had a postoperative BNI pain score of I, while one patient had a postoperative BNI pain score of II. The mean follow-up duration was 11 months. No permanent postoperative complications were observed.Conclusion: In this small retrospective case series, MVD was associated with complete or near-complete early pain relief in most patients. In patients with TN, the responsible arterial compression should be carefully investigated even when the trigeminal nerve is closely related to petrosal venous structures. Adequate arachnoid dissection and separation of the artery-nerve contact with a Teflon graft may contribute to adequate decompression.